STUDIES ON THE FORMULATION, PHYSICAL STABILITY, AND IN VITRO ANTIBACTERIAL ACTIVITY OF TEA TREE OIL (MELALEUCA ALTERNIFOLIA) NANOEMULSION GEL - Wulansari, Aprilla; Jufri, Mahdi; Budianti, Angky (International Journal of Applied Pharmaceutics, 2017)
Objective: This study aimed to formulate tea tree oil into a nanoemulsion gel dosage form and evaluate its physical stability and antibacterial activity. Methods: Nanoemulsion gels were formulated with various concentrations of tea tree oil, namely, 5%, 7%, and 9%, using Tween-80 as a surfactant and propylene glycol as a cosurfactant. The tea tree oil nanoemulsion gels showed a stable physical appearance over 8 weeks of storage at low temperature (4±2°C) and room temperature (25±2°C), cycling test, and centrifugation test. Results: The best formula was nanoemulsion gel formulation 1 (F1), which contained 5% tea tree oil, due to its good stability, smaller globule size, and greater viscosity. The results for antibacterial activity, determined by in vitro study, showed that the tea tree oil nanoemulsion gels exhibited antibacterial activity against Propionibacterium acnes through the formation of an inhibition zone. Conclusion: Higher concentrations of tea tree oil in nanoemulsion gels (5%, 7%, and 9%) showed greater mean inhibition zones (28.33±0.88 mm, 30.33±0.33 mm, and 31.67±0.33 mm, respectively).